Historiography of Nusantara Hadith Scholars - R. Rezeki Alam; Muhammad al-Mighwar; Engkos Kokasih (al-Afkar, Journal For Islamic Studies, 2025)
This article explores the journey of hadith historiography by Nusantara scholars, which is an important element in the understanding and development of Islam in the region. Using a historical approach and textual analysis, this study reveals how Nusantara scholars understood, narrated, and integrated hadith in a unique local context. The study begins with the historical background of the arrival of Islam in Nusantara, followed by the development of hadith studies brought by early scholars. In this article, it is emphasized how the process of adaptation and integration of hadith with local culture not only enriched the context of Nusantara Islam but also showed the uniqueness of hadith interpretation and application that differs from Islamic traditions elsewhere. Through textual analysis of various books by Nusantara scholars, this study highlights their methodology in verifying and narrating hadith, as well as its influence on the formation of Islamic identity in the region. This article also discusses the challenges and controversies faced by Nusantara scholars in their efforts to maintain the sanctity of hadith amidst changing social and cultural dynamics. Thus, this study provides insight into the significant contribution of Nusantara scholars to hadith historiography and their role in enriching global Islamic discourse.